Analisis Hidrologi Perencanaan Embung Bratayudha - Ai Rustini; Sulwan Permana (Institut Teknologi Garut, 2022)
Garut Regency is one of the areas in West Java Province which has a wet tropical climate, this causes quite high rainfall so there are several locations that often experience high overflows of water or commonly called floods. The construction of the reservoir is a step that can be taken in dealing with flooding that occurred in one of the areas in Garut, namely Jl. Bratayudha. The purpose of this study is to determine the type of reservoir that is suitable for the planning site and to determine the storage capacity of the reservoir using the hydrological analysis calculation method which includes planned rain using Normal Distribution, Normal Log 2 and 3 parameters, Gumbel type I and Pearson Log type III. The volume of the reservoir is determined by the inundation area of ​​the reservoir based on the elevation of the contour data on the topographic map. The final stage is to determine the construction material. The planning results of the Bratayudha Reservoir have an area of ​​6480 m² with a maximum volume of 15,552 m³ and a maximum elevation of 40.4 + m. The body of the reservoir, it is planned to be a river stone plaster wall covered with waterproof material and combined with reinforced concrete. The Bratayudha Embung is expected to be able to meet the irrigation needs of the residents' agricultural land. In addition, the location of the reservoir which is at a high ground level and has beautiful natural scenery is expected to become a new tourism object in Garut Regency.